Blood Bank Volunteer Application - Gunasegaran, Kanisha; Nurezayana Zainal, (Applied Information Technology And Computer Science, 2025)
Blood donation stands as a cornerstone of global healthcare, but in the evolving landscape of medical complexity, the integration of technology becomes imperative. This study explores the transformative potential of Blood Bank Volunteer Apps, emphasizing their vital role in saving lives during emergencies. In Malaysia, the active promotion of blood donation and the commitment of institutions like Sultan Abdul Halim Hospital underlines the significance of community engagement in healthcare. The identified problem of limited mobile access to critical blood donation information is addressed through a proposed Blood Bank Volunteer App. It aligns with the Rapid Application Development (RAD) model, ensuring a user-friendly application that streamlines blood donation processes for donors and healthcare institutions. In conclusion, this project leverages technology to facilitate regular blood donation, ultimately improving healthcare services and benefiting society as a whole.